Some reflections about quota system, curriculum and Biology teachers (Práxis Educativa, 2022)
The Universidade do Estado da Bahia (UNEB) is an important institution regarding affirmative actions, since, from 2002 on, it has implemented the quota system. The presentation of the difficulties of quota holders is a way to think about the relations between university, human rights and the right to quality education, contributing to discuss issues involving the curriculum of the teaching degree in Biology and teacher education. Thus, this text presents the difficulties that the quota students of the Biological Sciences course at UNEB find in different aspects, such as the cognitive, affective and social fields. To this end, a qualitative investigation was conducted, using a questionnaire from the Likert scale as a tool. It is concluded that it is necessary that the course undertake efforts to think of methodologies and inclusive evaluations, allowing the quota students to find support in this public space and become Biology teachers, subjects of rights.Keywords: Quota system. Affirmative actions. Biology teachers.